The Religius Diversity Space Formation Based Private Schools Affiliation in Malang City - Ibnu Mujib (Jurnal Sosiologi Pendidikan Humanis, 2021)
The intolerance that has threatened Indonesia in the last ten years is an important trail to show that the management of diversity in Indonesia is currently having a complex problem. Many parties are starting to question the wisdom of schools as a participatory diversity laboratory. This research emphasizes best practice tolerance education that is integrated into the realm of the learning curriculum in schools, this study more focused on three high school level schools in Malang city based on religion using a comparative descriptive method described by a qualitative critical approach. There is a perspective that is the finding of this research, namely the vision of tolerance and the definition of diversity built-in schools to give birth to patterns of student interaction in daily synergy with other different students. This perspective theoretically can produce five patterns of diversity interaction, namely: first: collegial interaction, second; dialogical experiment, third; intergroup community formation, fourth; participatory ethics, and fifth; transformative action. These five patterns were naturally formed by the vision of tolerance created by the three schools through various activities, both intra and extracurricular, and became patterns of intense participatory interaction in daily activities at school.